Pengembangan Media Pembelajaran Servis Bawah Bola Voli Menggunakan Modifikasi Bola Plastik Melalui Sasaran Botol Gantung pada Siswa SD Negeri 55 Palembang: Pengembangan, Model pembelajaran, servis bawah, bola plastik, botol gantung - Ariyani, Ariyani; Disurya, Ramanata; Nita, Perabu (ANTHOR: Education and Learning Journal, 2023)
Volleyball serve is the effort of a volleyball player to perform certain techniques in making theinitial shot in volleyball. In the study, there were still many obstacle factors put forward by elementary school students at SD Negeri 55 Palembang, such as laziness in implementing PJOK learning, boredom, and hands often feeling sore when doing underhand serve or playingvolleyball. This research is an R&D research using the ADDIE model (Analysis Design Development Implementation and Evaluation). The purpose of this study is for students to be happier and more active in carrying out PJOK learning in class IV SD Negeri 55 Palembang. The sample technique used by researchers is purposive sampling with a total of 16 students. The results of this study are in the form of validation data for volleyball experts, namely 92% of the categories in the research on developing learning media for serving volleyball using a modified plastic ball through a hanging bottle target are very valid and feasible to use and for student response questionnaires the percentage is 86.50% in the very valid category . In the development of the volleyball underserving learning model using a modification of a plastic ball through a hanging bottle target to students of SD Negeri 55 Palembang.